Impact of Word of Mouth and Purchase Decision on Brand Image of Viral Food within Marketing Strategy: A Systematic Literature Review - Nafisah, A’isy Fiklil; Soetjipto, Budi Eko (International Humanity Advance, Business & Sciences, 2025)
The contemporary marketing landscape emphasizes the importance of brand image and brand equity for competitive advantage. Viral food, fueled by digital technology and social media, presents a unique context where Word-of-Mouth (WOM) significantly influences consumer perception and purchase decisions, subsequently shaping brand image and equity. While existing research explores WOM, purchase decisions, brand image, and brand equity individually, a gap exists in understanding their integrated roles within the viral food phenomenon. This study addresses this gap by employing a Systematic Literature Review (SLR) to investigate how different forms of WOM and consumer purchase experiences uniquely contribute to the brand image and equity of viral food. Furthermore, it examines the strategic role of marketing efforts in leveraging WOM and influencing purchase decisions to build strong brand image and sustainable brand equity in this dynamic environment. This research aims to develop an integrated conceptual model and provide valuable insights for marketers in managing viral food brands and capitalizing on their often-fleeting popularity to build lasting brand equity. The findings will contribute to both theoretical understanding and practical application in the context of managing brands within temporary trends